2021
DOI: 10.1371/journal.pone.0249924
|View full text |Cite
|
Sign up to set email alerts
|

Maternal nutrient restriction in late pregnancy programs postnatal metabolism and pituitary development in beef heifers

Abstract: Maternal undernutrition during pregnancy followed by ad libitum access to nutrients during postnatal life induces postnatal metabolic disruptions in multiple species. Therefore, an experiment was conducted to evaluate postnatal growth, metabolism, and development of beef heifers exposed to late gestation maternal nutrient restriction. Pregnancies were generated via transfer of in vitro embryos produced using X-bearing sperm from a single Angus sire. Pregnant dams were randomly assigned to receive either 100% (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…While the cows in the MUD treatment consistently lost BW each week and lost body condition over the treatment period, we reject our hypothesis, as we did not observe this same decrease in 12th rib back-fat thickness. Long et al (2021) , however, did observe a decrease in 12th rib back-fat and ribeye area when mature cows were nutrient restricted to 70% of the NASEM (2016) recommendations for total net energy requirements from day 158 of gestation until parturition. In this study of Long et al (2021) , however, it is unclear if net energy requirements were adjusted daily or weekly for each individual cow.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…While the cows in the MUD treatment consistently lost BW each week and lost body condition over the treatment period, we reject our hypothesis, as we did not observe this same decrease in 12th rib back-fat thickness. Long et al (2021) , however, did observe a decrease in 12th rib back-fat and ribeye area when mature cows were nutrient restricted to 70% of the NASEM (2016) recommendations for total net energy requirements from day 158 of gestation until parturition. In this study of Long et al (2021) , however, it is unclear if net energy requirements were adjusted daily or weekly for each individual cow.…”
Section: Discussionmentioning
confidence: 76%
“… Long et al (2021) , however, did observe a decrease in 12th rib back-fat and ribeye area when mature cows were nutrient restricted to 70% of the NASEM (2016) recommendations for total net energy requirements from day 158 of gestation until parturition. In this study of Long et al (2021) , however, it is unclear if net energy requirements were adjusted daily or weekly for each individual cow. Additionally, the authors state that requirements were estimated per individual based on BW.…”
Section: Discussionmentioning
confidence: 76%
“…Two other studies found no effect of dietary restriction in late gestation on BTW, even though this is the time of maximum growth of the fetal calf [ 60 , 61 ]. However, BTW was reduced in both restrict fed pregnant NP heifers [ 62 , 63 ] and in PP heifers [ 64 ]. These results support the hypothesis that animals which are still growing partition available nutrients differently to mature cows, prioritising themselves over their fetus.…”
Section: Impact Of Fetal Programming On Size At Birth and Post-natal ...mentioning
confidence: 99%
“…Undernourishment also caused an increase in fibrosis in adipose tissue and the occurrence of a subpopulation of very small adipocytes. Other studies in both sheep [ 75 ] and beef heifers [ 63 ] similarly found that offspring born to dams which had been nutritionally restricted during pregnancy had increased internal fat when slaughtered. The lambs also tended to have proportionately reduced muscle weights.…”
Section: Influence Of Fetal Programming On the Development Of Specifi...mentioning
confidence: 99%
“…Nutrient insults in late gestation would be expected to have the greatest impact on fetal size (i.e., birth weight and body length), as almost 75% of ruminant fetal growth occurs at this stage ( Du et al, 2010 ; Funston et al, 2010 ). Several studies have shown that nutrient insults during the last two-trimesters of a pregnancy can reduce fetal growth, birth weight, as well as number of muscle fibres and adipocytes in the offspring of sheep and cattle ( Reed et al, 2007 ; Swanson et al, 2008 ; Du et al, 2010 ; Funston et al, 2010 ; Vonnahme et al, 2015 ; Long et al, 2021 ). Therefore, any decrease in birth and body weight because of nutrient insults at these later stages of pregnancy can lead to an impairment of adipogenesis and myogenesis as well as a decrease in muscle fibre growth ( Du et al, 2010 ; Funston et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%